Simulation of agronomic and nitrate pollution related parameters in vegetable cropping sequences in Mediterranean greenhouses using the EU-Rotate_N model - Soto Bravo, Freddy (2018)
The capacity of the EU-Rotate N model to simulate agronomic parameters (dry matter production, yield,crop N uptake, evapotranspiration (ETc), soil water content dynamics) and parameters associated tonitrate (NO3−) pollution (drainage, NO3−leaching, accumulation of mineral N in soil) was evaluatedin sequences of melon and pepper crops grown in plastic greenhouses. Simulated values of all outputvariables were compared to measured values. Two sequences with either conventional or improvedmanagement for water and N were examined during the 2005 and 2006 cropping seasons. Additionally,simulation of drainage and NO3−leaching was evaluated during the period between crops followingirrigations associated with soil disinfection and leaching of accumulated salts. Calibration of parametersrelated to crop growth, the critical N curve and ETcconsiderably improved simulation of drainage, NO3−leaching and of soil water and soil mineral N dynamics. Following calibration, the EU-Rotate N modelaccurately simulated dry matter production, crop N uptake and marketable fruit yield; the simulationerrors being lower or similar to those reported elsewhere. ETcand drainage were accurately simulated inthe 2006 melon and pepper crops and in the 2005 melon crop; they were respectively over- and under-estimated in the 2005 pepper crop probably on account of a virus infection. EU-Rotate N accuratelysimulated soil water content for the 0−30 and 30−60 cm soil layers. Soil mineral N and NO3−leachingwere generally underestimated by EU-Rotate N, the error being larger in the 2005 sequences; however,the model effectively simulated seasonal trends.